Balanced harvesting is the bioeconomic equilibrium of a size-structured Beverton-Holt model. (28th September 2016) - Plank, Michael J.
Abstract : Balanced harvesting (BH) was introduced as an alternative strategy to size-at-entry fishing with the aim of maintaining ecosystem structure and functioning. BH has been criticized on a number of grounds, including that it would require an infeasible level of micromanagement and enforcement. Recent results from a size-spectrum model show that the distribution of fishing mortality across body sizes that emerges from the behaviour of a large number of fishing agents corresponds to BH in a single species. Size-spectrum models differ from classical size-structured models used in fisheries as they are based on a bookkeeping of biomass transfer from prey to predator rather than a von Bertalanffy growth model. Here we investigate a classical Beverton-Holt model coupled with the Gordon-Schaefer harvesting model extended to allow for differential fishing pressure at different body sizes. This models an open-access fishery in which individual fishing agents act to maximize their own economic return. We show that the equilibrium of the harvesting model produces an aggregate fishing mortality that is closely matched to the production at different body sizes, in other words BH of a single species. These results have significant implications because they show that the robustness of BH does not depend on arguments about the relative production levels of small versus large fish.